2022
DOI: 10.1108/jices-06-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Fear of missing out (FOMO) to the joy of missing out (JOMO): shifting dunes of problematic usage of the internet among social media users

Abstract: Purpose With the rapid improvement in digital infrastructure, the popularity of digital devices and smartphones in every pocket, the yearning to stay connected with others has increased manifold, especially in youngsters. This has raised multiple concerns primarily related to the problematic usage of the internet (PUI). The current research study aims to scrutinize the association between PUI, psychological and mental health (PMH), social media fatigue (SMF), fear of missing out (FOMO), desire to disconnect (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…There are positive effects associated with FoMO behavior despite its association with negative emotions such as anxiety, depression, and impulsivity. This finding supports the study of Rautela and Sharma (2022) and Zendle and Bowden-Jones (2019). One example is informationseeking behavior involving fresh products, services, or experiences.…”
Section: Figure 3 Validated Research Modelsupporting
confidence: 86%
See 1 more Smart Citation
“…There are positive effects associated with FoMO behavior despite its association with negative emotions such as anxiety, depression, and impulsivity. This finding supports the study of Rautela and Sharma (2022) and Zendle and Bowden-Jones (2019). One example is informationseeking behavior involving fresh products, services, or experiences.…”
Section: Figure 3 Validated Research Modelsupporting
confidence: 86%
“…The prevalence of FoMO, or the fear of missing out, has been intensified by increased social media usage and excessive sharing of personal information. This phenomenon is often described as an addiction to online networking (Rautela & Sharma, 2022;Zendle & Bowden-Jones, 2019). Fear of Missing Out (FoMO) is frequently linked to maladaptive psychological functioning, such as heightened levels of anxiety (Argan & Argan, 2019).…”
Section: Fear Of Missing Outmentioning
confidence: 99%
“…This outcome aligns with prior research (see Kang et al, 2019) that has demonstrated excessive conformist consumption behavior where high FOMO enacts a strong tendency and willingness to conform to group behavior. Earlier research has examined the phenomenon of FOMO across various consumption scenarios (Çelik et al, 2019; Rautela & Sharma, 2022; Tandon et al, 2021), revealing that FOMO is likely to elicit greater and more intense following‐driven behavior (Gartner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the FOMO phenomenon having long‐standing recognition in popular media (Hodkinson, 2019), the psychological mechanisms underlying linkages to consumer purchasing behavior have only recently been researched (see a review of the current literature in Tandon et al, 2021). Empirical evidence suggests that FOMO, as an anticipatory emotion, can explain individual decision‐making and corresponding behavior, including heavy media use (Hunt et al, 2018), WhatsApp use (Blackwell et al, 2017; Rautela & Sharma, 2022; Sha et al, 2019), and online purchasing (Çelik et al, 2019; Good & Hyman, 2020; Van Solt, 2019). Most scholars, follow the conceptualization of Przybylski et al (2013), who described FOMO as the uneasy feeling that others might have better (i.e., more rewarding or beneficial) “experiences.”…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Apaolaza et al [ 43 ] also confirmed that compulsive mobile SNS use induces stress. Rautela and Sharma [ 44 ] showed that compulsive use significantly and positively impacts mental and psychological health. Therefore, this study assumed that high compulsive use of social media is positively associated with a high technology overload and the technological intrusion of social media.…”
Section: Hypothesesmentioning
confidence: 99%